Aid Is Good for the Poor - Hirano, Yumeka; Otsubo, Shigeru (World Bank Group, Washington, DC, 2014)
Aid is good for the poor. This paper uses detailed aid data spanning 60 developing countries over the past two decades to show that social aid significantly and directly benefits the poorest in society, while economic aid increases the income of the poor through growth. This new and unequivocal finding distinguishes the current study from past studies that only utilized aggregate aid data and returned ambiguous results. The paper also confirms that none of the elements of globalization (trade, foreign direct investment, remittances), policies (government expenditure, inflation management), institutional quality, nor other plausibly pro-poor factors have systematic effects on the poor or any other income group, beyond their effects on average incomes. The paper finds that trade and foreign direct investment tend to benefit the richest segments of society more than other income groups. Therefore, the presented evidence suggests that aid can play a crucial role in enabling the poor to benefit more from globalization. These discoveries underscore the need to assist developing countries to find the mix of economic and social aid that jointly promotes the participation of the poor in the development process under globalization. In this manner, aid can make greater strides in spurring development.